2014
DOI: 10.1371/journal.pone.0089566
|View full text |Cite
|
Sign up to set email alerts
|

Care and Feeding of the Endocannabinoid System: A Systematic Review of Potential Clinical Interventions that Upregulate the Endocannabinoid System

Abstract: BackgroundThe “classic” endocannabinoid (eCB) system includes the cannabinoid receptors CB1 and CB2, the eCB ligands anandamide (AEA) and 2-arachidonoylglycerol (2-AG), and their metabolic enzymes. An emerging literature documents the “eCB deficiency syndrome” as an etiology in migraine, fibromyalgia, irritable bowel syndrome, psychological disorders, and other conditions. We performed a systematic review of clinical interventions that enhance the eCB system—ways to upregulate cannabinoid receptors, increase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 327 publications
(362 reference statements)
4
95
0
2
Order By: Relevance
“…Acupuncture combined with electroacupuncture could decrease plasma glutamate levels, which were found significantly increased in rats during acute migraine attacks, and thereby relieving pain [55]. Endocannabinoid system activation, which has been proven to exert analgesia and neuroprotection [56, 57] is believed to be another mechanism of action of acupuncture on migraine patients [58]. …”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture combined with electroacupuncture could decrease plasma glutamate levels, which were found significantly increased in rats during acute migraine attacks, and thereby relieving pain [55]. Endocannabinoid system activation, which has been proven to exert analgesia and neuroprotection [56, 57] is believed to be another mechanism of action of acupuncture on migraine patients [58]. …”
Section: Discussionmentioning
confidence: 99%
“…This role is also witnessed by the plethora of conventional and nonconventional therapies that have been reported to modify endocannabinoid tone (557). As a consequence, it should not be surprising to see that 1) activation of CB1 or CB2 often produces biphasic or even opposing effects on a given physiological response depending on the "starting" state of the system; 2) tissue endocannabinoid levels also often change in a biphasic manner during some prolonged pathological deviations from the physiological steady state; 3) pharmacological manipulation of either CB1/CB2 activity or endocannabinoid levels through inhibition of biosynthetic or inactivating mechanisms might either help restore homeostasis or exacerbate the effects of the perturbation, depending on where (what cell) and when (what disease stage) it is effected; and 4) even in those cases in which endocannabinoids always play a protective role throughout disease progression, the multiplicity of their molecular targets and metabolic pathways (the latter of which are often in common with other mediators acting at other targets), makes it difficult to globally acting CB1/CB2 agonists/antagonists, or selective inhibitors of endocannabinoid degradation or biosynthesis, to produce safe and efficacious therapeutic effects.…”
Section: Physiopathopharmacology Of Phyto/endocannabinoidsmentioning
confidence: 98%
“…However, strong side effects on mood for some patients lead to the withdrawal of rimonabant from the market. In this context, dietary PUFAs appeared as homeostatic regulators of endocannabinoids [95], encouraging researchers to investigate the effect of ω-3 rich diet on obesity. It has been shown that a diet rich in ω-3 leads to weight loss, in parallel to a decrease of AEA and 2-AG [88,93].…”
Section: Endocannabinoids Derived From ω-3 Pufasmentioning
confidence: 99%
“…Even if cannabis has been used for decades as a self-medication to dampen stress and anxiety, only few clinical studies so far have tried enhancement of endocannabinoid signaling as a potential therapeu-tics to treat mood and anxiety disorders [149,150]. This may be due to the potential side effects of directly targeting the endocannabinoid system, and in this context dietary PUFAs, as homeostatic regulators of endocannabinoids [95], could constitute a very interesting and promising therapeutic candidate to target the endocannabinoid system. From these studies, it thus appears that both dietary PUFAs and endocannabinoids play a role in mood and anxiety disorders and the link between both has been made only in our laboratory in preclinical studies.…”
Section: Pufas / Endocannabinoids Interactions In Mood and Anxiety DImentioning
confidence: 99%